2010
DOI: 10.1007/s00467-010-1599-6
|View full text |Cite
|
Sign up to set email alerts
|

Gout in pediatric renal transplant recipients

Abstract: Clinical gout has rarely been described after pediatric renal transplantation (RTx), although asymptomatic hyperuricemia is common in these patients. We describe three male pediatric patients who presented with gouty arthritis 7-8.5 years following RTx. Since receiving allopurinol, all patients had been free of gouty symptoms. To prevent severe bone marrow depletion, the dosage of azathioprine, an immunosupressant drug, was reduced by 50% to prevent interaction with allopurinol. Because atypical presentation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…All patients with gout in our study were found to have at least one underlying disorder. Previous case reports have shown that gout in children or adolescents was associated with comorbidities such as Down syndrome [11], glycogen storage disease [12], renal transplantation [13], leukemia [14], and methyl malonic acidemia [15] (Table 2).…”
Section: Conditions Causing Hyperuricemiamentioning
confidence: 99%
See 1 more Smart Citation
“…All patients with gout in our study were found to have at least one underlying disorder. Previous case reports have shown that gout in children or adolescents was associated with comorbidities such as Down syndrome [11], glycogen storage disease [12], renal transplantation [13], leukemia [14], and methyl malonic acidemia [15] (Table 2).…”
Section: Conditions Causing Hyperuricemiamentioning
confidence: 99%
“…Several drugs such as diuretics (thiazide), anticonvulsants (valproate and phenobarbital), cyclosporine, theophylline, and pyrazinamide have been reported to increase uric acid levels in children and adolescents [1, 13, 3941]. Although the underlying causes are not fully understood, renal tubular reabsorption of uric acid, dehydration, and increased purine catabolism has been postulated [1, 42].…”
Section: Conditions Causing Hyperuricemiamentioning
confidence: 99%
“…The risk of bone marrow depletion is increased in patients with low thiopurine methyl-transferase activity. To avoid the serious myelosuppression during treatment of hyperuricemia and gout, substantial reduction of azathioprine dose (by at least 50%) is required when allopurinol is given concomitantly, or alternative agents other than allopurinol should be considered [142][143][144].…”
Section: Treatment Of Hyperuricemiamentioning
confidence: 99%
“…Another study in China has shown a high prevalence of hyperuricemia in children of age 3-6 years, male gender, and a strong association with high diastolic blood pressure (DBP) and increased triglycerides concentration [ 5 ]. Hyperuricemia can occur as a side effect of several drugs like some antiepileptics, with valproate and phenobarbital being the commonest ones; thiazide diuretics, cyclosporine, theophylline, and pyrazinamide have also been reported as the main causative factors, with their mechanism not fully understood [ 6 ].…”
Section: Introductionmentioning
confidence: 99%